The last batrachideine of Europe: A new genus and species of pygmy grasshopper (Orthoptera: Tetrigidae) from Eocene Baltic amber - Thomas, M. Jared; Skejo, Josip; Heads, Sam W. (Zootaxa, 2019)
A new genus and species of pygmy grasshopper (Orthoptera: Tetrigidae) is described from Eocene Baltic amber. Danatettix hoffeinsorum gen. et sp. nov. is assigned to the subfamily Batrachideinae based on antennae with more than 19 antennomeres, sulcate mesofemora, and rectangular paranota. This species is readily distinguished from other batrachideines by a markedly produced vertex, pronotum with divergent internal and external lateral carinae, and highly setiferous female lateral basivalvular sclerite with scabrose integument. The morphology of Danatettix suggests placement within the here defined Tettigidea genus group (comprising Eutettigidea Hancock, 1914, Paurotarsus Hancock, 1900, and Tettigidea Scudder, 1862) and suggests that the latter had diverged from the new Scaria genus group (comprising Eotetrix Gorochov, 2012, Rehnidium Grant, 1956 and Scaria Bolívar, 1887) by the Early Eocene.